Kaczynski, Steve and Scott Duke Kominers. The Everything Token: How NFTs and Web3 Will Transform the Way We Buy, Sell, and Create - Vohra, Rakesh (Journal of Economic Literature, 2025)
Rakesh Vohra of University of Pennsylvania reviews “The Everything Token: How NFTs and Web3 Will Transform the Way We Buy, Sell, and Create” by Steve Kaczynski and Scott Duke Kominers. The Econlit abstract of this book begins: “Explores how non-fungible tokens (NFTs) are changing the way that business is done, demonstrating the role and inevitability of NFT technology in everyday life.”